Connecting Afghanistan : A Policy Note on Rural Access in Afghanistan - World Bank (Washington, DC, 2014)
The objectives of this rural access policy note are to: (i) provide a first-level analysis of rural access issues in Afghanistan, (ii) identify key issues, achievements, and challenges in the provision of rural access, (iii) make recommendations for the Government's rural access policy, and (iv) stimulate the policy dialogue on provision of rural access between the Government of Afghanistan and stakeholders including civil society, non-governmental organizations (NGOs), development partners, and private enterprise. Nearly 80 percent of Afghanistan's people live in rural areas. Incidence of rural poverty is high as the country recovers from the long-term effects of the nearly thirty years of conflict and a recently ended six-year drought. The insurgency in some parts of the country continues to hamper development efforts. As lack of rural access is one of the sources of rural poverty, and holds back the replacement of the poppy economy with licit rural livelihoods, the World Bank has supported the provision of rural roads to improve rural accessibility. Many of these recommendations are cross-cutting; to plan and implement them would involve several ministries. Investments and recurrent expenditures in rural access are substantial and should be leveraged in the most effective manner. It is therefore recommended that the Ministry of Finance take the lead in bringing this policy note to the attention of Government, donors, and other actors.